The Impact of Fossil Energy Subsidies on Social Cost in Indonesia - Sasana, Hadi; Salman, F.; Suharnomo, Suharnomo; Nugroho, S. B. M.; Yusuf, A. G. Edy (International Journal of Energy Economics and Policy, 2018)
Subsidies for energy have driven the consumption of fossil energy to increase sharply. The increased use of fossil energy will increase social costs and negatively affect the environment. This study investigated the impact of fossil energy subsidies on social costs in Indonesia. The analysis used was multiple regression using secondary data from the World Bank and Ministry of Finance of the Republic of Indonesia. The results of the study showed that energy subsidies and air pollution (CO2) in Indonesia have led to increased social costs. Meanwhile, the use of renewable energy has a negative effect on social costs in Indonesia. Keywords: Energy subsidy, air pollution (CO2), renewable energy, social cost JEL Classifications: Q42, Q43